2013
DOI: 10.1371/journal.pone.0080841
|View full text |Cite
|
Sign up to set email alerts
|

Phytoceramide in Vertebrate Tissues: One Step Chromatography Separation for Molecular Characterization of Ceramide Species

Abstract: Ceramide is a precursor for complex sphingolipids in vertebrates, while plants contain phytoceramide. By using a novel chromatography purification method we show that phytoceramide comprises a significant proportion of animal sphingolipids. Total ceramide including phytoceramide from mouse tissue (brain, heart, liver) lipid extracts and cell culture (mouse primary astrocytes, human oligodendroglioma cells) was eluted as a single homogenous fraction, and then analyzed by thin layer chromatography, and further c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Cers and SMs had a similar acyl chain profiles (Figure 5(a) and (b)), but the galactosylceramides had a different profile (Figure 5c), which was very rich hydroxylated species with the longer chains (29)(30), otherwise known as cerebrosides. Phytoceramides were not observed in our sample at this time though it should be contained in the brain (31).…”
Section: Measurement Of Total Brain Extractmentioning
confidence: 55%
“…Cers and SMs had a similar acyl chain profiles (Figure 5(a) and (b)), but the galactosylceramides had a different profile (Figure 5c), which was very rich hydroxylated species with the longer chains (29)(30), otherwise known as cerebrosides. Phytoceramides were not observed in our sample at this time though it should be contained in the brain (31).…”
Section: Measurement Of Total Brain Extractmentioning
confidence: 55%
“…Using liquid chromatography–tandem mass spectrometry (LC-MS/MS), we found that Chlamydomonas generates very long chain C26:0 (11 ± 3 pmol/mg cells) and C28:0 (8 ± 2 pmol/mg cells) phytoceramides, which are common plant sphingolipids ( Figure 2C ). In comparison, glial cells contain relatively small proportions of phytoceramide (<10% of total ceramides; Dasgupta et al. , 2013 ) but larger amounts of ceramide (800 ± 150 pmol/mg cells), with C18:0 ceramide (35%) and C24:1 ceramide (25%) being the most abundant ( Wang et al.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that phytoceramide (ceramide NP) was produced through conversion of dihydroceramide by DES2 (Mizutani et al, ). Dasgupta’s group found that DES2 was expressed in various tissues such as skin, kidney, and heart, as well as phytoceramide was detected in these tissues (Dasgupta et al, ). In this research, the expression of DES2 was exceptionally increased by PHS treatment.…”
Section: Discussionmentioning
confidence: 99%